Assessing the Association Between Lead Pollution and Risk of Alzheimer’s Disease by Integrating Multigenomics - Li, Chunying; Zhang, Yuwei; Liang, Jiandong; Wu, Changyan; Zou, Xiao (Frontiers in Neuroscience, 2022)
Alzheimer disease (AD) is a life-threatening neurodegenerative disease of the elderly. In recent observations, exposure to heavy metal environmental may increase the risk of AD. However, there are few studies on the causal relationship between heavy metal exposure and AD. In this study, we integrated two large scale summary AD genome-wide association studies (GWAS) datasets and a blood lead level GWAS dataset, and performed the two sample mendelian randomization analysis to assess the causality of blood lead level and AD risk. The results showed that there is a significant positive causality between blood lead level and AD risk both in the inverse-variance weighted (IVW) model and the weighted median estimator (WME) model. An independent additional verification also reached a consistent conclusion. These findings further confirm the conclusions of previous studies and improve the understanding of relationship between AD pathogenesis and toxicity of lead in environmental pollution.